François Gros (1925–2022) - Petit, Christine; Kourilsky, Philippe (Comptes Rendus Biologies, 2024)
François Gros, a biologist by training, began his research at the Institut Pasteur. In 1961, he discovered the molecular nature of the proposed intermediary between the gene and the protein, a so-called messenger RNA (mRNA), and determined its main characteristics. The author of numerous books, François Gros has helped shape and enlightened the birth of molecular biology and the development of related biotechnologies since the 1970s. He was Professor at the Collège de France and Permanent Secretary of the French Academy of Sciences. Within the Academy, he initiated the creation of a committee for developing countries (COPED). François Gros was a humanist driven by moral rigour and an unfailing sense of commitment.